2012
DOI: 10.1017/s0007114512000384
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short-term genistein intervention on prostate biomarker expression in patients with localised prostate cancer before radical prostatectomy

Abstract: Nutritionally relevant levels of genistein, the predominant isoflavone in soyabean associated with lower risk of prostate cancer (PCa), may modulate the expression of prostate tissue biomarkers associated with cancer prediction and progression. A phase 2 placebocontrolled, randomised, double-blind clinical trial was conducted in forty-seven Norwegian patients before prostatectomy. Intervention was 30 mg genistein or placebo capsules daily for 3 -6 weeks. Luminal cells from malignant and benign glands were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 37 publications
0
33
0
1
Order By: Relevance
“…In a double-blind placebo-controlled study, green tea catechins (GTC) significantly prevented prostate cancer development in men with highgrade premalignant prostate intraepithelial neoplasia (42). Two randomized, double-blind, placebo-controlled short-term isoflavone intervention trials before radical prostatectomy have shown that genistein failed to change the PSA levels significantly, even though it modulated the expression of several genes involved in prostate cancer (43,44). A 6-month double-blind, placebo-controlled intervention study with highdose soy extracts conducted in 53 men with prostate cancer enrolled in an active surveillance program also failed to show lower PSA levels (45).…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind placebo-controlled study, green tea catechins (GTC) significantly prevented prostate cancer development in men with highgrade premalignant prostate intraepithelial neoplasia (42). Two randomized, double-blind, placebo-controlled short-term isoflavone intervention trials before radical prostatectomy have shown that genistein failed to change the PSA levels significantly, even though it modulated the expression of several genes involved in prostate cancer (43,44). A 6-month double-blind, placebo-controlled intervention study with highdose soy extracts conducted in 53 men with prostate cancer enrolled in an active surveillance program also failed to show lower PSA levels (45).…”
Section: Discussionmentioning
confidence: 99%
“…A randomized control study of 158 men in eight Japanese centers using a purified isoflavone supplement reported no significant change in the PSA value before and after treatment, and the incidence of PCa showed no significant difference between isoflavone and placebo groups, although for patients aged >65 years, PCa incidence in the isoflavone group was significantly lower (28.0% vs. 57.1%) [116]. Reports of isoflavone supplementation in patients with PCa include multiple randomized controlled trials that suggest that isoflavones show a suppressive effect on PCa progression based on biomarkers, such as serum PSA and testosterone levels [117][118][119][120], although the results have been inconsistent [121]. Such inconsistencies might be related to differences in dosage, duration, and dietary intake by the cohorts in each study.…”
Section: Isoflavonesmentioning
confidence: 97%
“…Phase I and II studies investigating the clinical activity of genistein and other soy isoflavones compounds in cancer treatment and chemoprevention have been published with disappointing results [6365]. …”
Section: Wnt Inhibitors In Clinical Developmentmentioning
confidence: 99%